Investigation of some thermophysical properties of Asphodelus aestivus reinforced polyester composite - Orhan, Ramazan; Aydoğmuş, Ercan (Fırat University, 2022)
In this research, both environmentally friendly and economical composites have been produced by using biomass wastes in unsaturated polyester. The use of renewable biomass wastes as a filler in unsaturated polyester is reduced the carbon footprint of the composite obtained. A low-density and flexible structure could be achieved according to the intended use of polyester composites. While the density of the pure polyester polymer not reinforced with biomass is around 1206 kg/m3, the density of the 5 wt.% filler added composite decreases to 1167 kg/m3. Biomass waste (Asphodelus aestivus L.) reduces Shore D hardness of the polyester composite and turns it into a more flexible and easy-to-process material. It has been observed that the thermal conductivity coefficient of the biomass reinforced polyester composite shows a slight increase compared to the pure polyester composite. Besides, it has been determined that as the amount of biomass in the polyester composite increases, the activation energy decreases. The specific bond structure in the polyester polymer has been determined by Fourier transform infrared (FTIR) spectroscopy. Biomass waste is not making a chemical bond with polyester, it is only used as a filler. Also, the surface morphology of the polyester composite has been investigated with the help of scanning electron microscopy (SEM). The use of 3 wt.% Asphodelus aestivus L. biomass as a filler does not create a negative pore structure on the composite surface.
Keywords: Chemical Engineering; Kimya Mühendisliği